Effects of Foliar Nutrition on Onion Seed Storage under Modified Atmosphere Packages - S. A., S. A.; Hashem, M. Y.; Mahmoud, G. I.; Abd El-Gawad, K. F.; El-Ramady, H. R.; Alshaal, T. A.; Domokos-Szabolcsy, É.; Elhawat, N.; Prokisch, J.; Fári, M. (International Journal of Horticultural Science, 2013)
Modified atmosphere packaging (MAP) and controlled atmosphere storage techniques to reduce the oxygen around the food are largely used for the preservation of fresh produce. There have been great technological advances in this area of preservation, particularly as it refers to improving the quality and shelf-stability of highly perishable food products, such as produce. Two successive winter seasons of 2008/2009 and 2009/2010 were conducted under sandy soil conditions to study the effect of spraying with 12 commercial compounds on onion seeds storage under modified atmosphere packages. Germination percent of seeds decreased in 5°C than storage in room temperature. Germination percent of seeds was gradually decreased with increasing the storage period. Packaging treatments had a significant effect on germination percent of seeds. All the packaging treatments had the higher germination percent than the paper package (control). The highest germination percent after 12 months of storage was recorded for the treatment with non perforated polypropylene in room temperature and polyethylene and non perforated polypropylene in 5°C. Catalase activity decreased with the prolongation of storage period. The non perforated polypropylene package had the highest catalase activity. The treatment with non perforated polypropylene had the highest catalase activity after 12 months of storage in both room and 5°C temperatures. Peroxidase activity of seeds was gradually decreased with increasing the storage period. The highest peroxidase activity after 12 months of storage was recorded in non perforated polypropylene in both storage temperatures.